Envelhecimento populacional e previdência social: a questão social da longevidade e o financiamento dos sistemas previdenciários, sob a ótica do princípio da solidariedade social - NASSAR, Elody Boulhosa (Universidade Federal do Pará, 2017)
The central theme of this work is population aging and its pivotal correlation to longevity and social security funding. The longevity that is so intensely pursued is a factor of concern in contemporary society vis-à-vis related social questions of oldness and social protection in the area of the social security. This work is divided in six chapters. The first chapter ponders on the correlation between the progression of time and its consequences on the decline of human beings, as a basic notion for the understanding of the oldness. The second chapter examines the meaning of the concepts related to aging as well as of the newly emerging expressions on the diversity of oldness by underscoring the use of chronological criterion as the parameter for the legal definition of the concept of the old. In the third chapter, the definition of the social issue of the aging is studied. This definition is examined through a statistical analysis related to the new and growing social group that requires adaptations of the civil society, the family and government. In this context, the condition of women is also treated by pointing out differences in the oldness between the genders. In the fourth chapter, the emphasis is on the social achievements related to aging in light of the legitimation and justification of social rights of Social Security as an effective means of social inclusion and achieving dignity at old age. In the fifth chapter, it is demonstrated that new social questions emerge from the aging of the world population. Consequently, new social, political and economic questions demand novel policies by the government in order to guarantee the quality of life of the aging as a fundamental human right. In the sixth chapter, solidarity is suggested as the fundamental postulate upon which the principles of social security are based. Moreover, solidarity is argued to be the central logic of any pension plan and that it conflicts with the logic of the market or science. This work utilizes extensive, interdisciplinary, national bibliography on the various issues contained in the chapters of the thesis, as well as foreign doctrine, with emphasis on the legal literature, as the base of support of the arguments above-mentioned. It is concluded that social security reforms and the neoliberal preaching defense of capitalization do not take into account the issue of equity in formulating policies for Social Security and that the State should be the main responsible for guaranteeing fundamental social rights. This thesis advocates that, in the case of the elderly, solidarity is an ethical requirement, and above all, an ethic of urgency.